(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Causes of chronic renal failure may vary in different parts of the world and in the same place at different times. Knowing the causes is important in planning prevention and treatment. Objective: Is to find the causes of chronic renal failure in Al-Kadhimiya Teaching Hospital (Baghdad), which may serve as a representative of other major general hospitals in the country. Patients & Methods: We studied 145 patients (98 males and 47 females). Their ages ranged from 1 to 80 years. The cause of renal failure in each patient was defined according to preset criteria. When the cause could not be identified in spite of satisfactory clinical examination and investigations it was labeled unknown. Results: The cause was unknown in 27.5% of patients. Known causes included: obstructive nephropathy (17.1%), diabetes mellitus (16.5%), primary hypertension (15.1%) and reflux nephropathy (13.1%). A definite diagnosis of glomerulonephritis could be ascertained in 6 patients only. Conclusion: The cause of chronic renal failure could not be identified in a significant proportion of patients many of whom may have been suffering from undiagnosed chronic glomerulonephritis. Among identifiable causes urinary tract obstruction, diabetes mellitus, primary hypertension and reflux nephropathy (chronic pyelonephritis) were the leading causes. Key words: Renal failure, glomerulonephritis, diabetes, hypertension. Iraqi J Med Sci, 2004; Vol. 3 (1): 47-50